Theoretical and experimental infrared spectra of hydrated and dehydrated nafion. Issue 18 (23rd July 2013) - Kendrick, Ian; Yakaboski, Adam; Kingston, Erin; Doan, Jonathan; Dimakis, Nicholas; Smotkin, Eugene S.
ABSTRACT The time‐dependent IR spectra during dehydration of fully hydrated Nafion show the reversible disappearance of the 1061 cm−1 and 969 cm−1 concurrent with the emergence of peaks at ∼928 cm−1 and ∼1408 cm−1. The first pair of group modes is associated with a dissociated exchange group (sulfonate) with a local C3V symmetry. The C3V group modes shift with state‐of‐hydration: The 969 cm−1 peak completely vanishes and the 1061 cm−1 is reduced to a small shoulder at 1070 cm−1 at end of dehydration. The C3V group modes are replaced by the pair of group modes of an associated exchange group (sulfonic acid) with C1 local symmetry. The density functional theory normal mode analysis confirms that the sulfonic acid/sulfonate site plays a dominant role in the C1 and C3V group modes, respectively. This work clarifies the importance of assigning fluoropolymers peaks as group modes rather than traditional single functional group assignments as is often the case with the ∼1061 cm−1 and ∼969 cm−1C3V group modes. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1329–1334